Pesan Singkat Film Budi Pekerti: Beretika dalam Bermedia - Muttafaqur Rohmah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research discusses the meaning, messages and wisdom displayed by the characters in the film Budi Pekerti. Just like a show, the requirements for meaning and message are also the mandate and wisdom to depict and emulate attitudes, acting and human behavior in life as the meaning and function of a good film. It contains signs that contain many lessons. That's what the film Budi Pekerti wants to convey. Characteristics is not just a film title, but also morals in its plural and real meaning. The morals contained in the nation's values are the values of Pancasila. Good manners in using social media and ethical and wise use of social media. Character films are a long bridge whose end is not yet visible. As if describing the faces of social media and netizens who are always correct with all their posts. In this research, the author dissects the imagination of young filmmakers in Indonesia who not only present love stories, but also social criticism of society. This film is a "thinking" film made by young filmmakers in Indonesia who elevates the level of Indonesian films not only about love and ghosts. Being wise in media is a short message that this film wants to highlight. The posts and handprints of netizens who don't know the truth have actually become the absolute truth. Because truth in social media is not determined by the actual truth, but by the number of posts and threads, feeds or stories on social media. The virtual world dominates the real world. The digitalization of thinking and the freezing of human ethics is the main point that humans sometimes believe more in the words of the media, rather than honest words that come out of the mouths of other humans.